A Biological Survey for the Nation - National Research Council (The National Academies Press, 1994)
Our country has long recognized the importance of its biological resources but we often lack sufficient scientific knowledge to make wise decisions. This realization has led to calls for new ways of providing this information, including the formation of a national biological survey. This volume discusses key issues and problems for which an improved assessment of the nation's biological resources is needed; the kinds of efforts in research and information management needed to create that assessment; and how government, private organizations, and individuals can work together to meet the needs identified. Policymakers, resource managers, public interest groups, and researchers will find this book useful as they participate in the national dialogue on this topic and take actions to implement the needed survey activities.

Future Roles and Opportunities for the U.S. Geological Survey - National Research Council (The National Academies Press, 2001)
The U.S. Geological Survey (USGS) has adapted to the changing political, economic, and technical state of the nation and the world since it was established in the late nineteenth century. Over a period of more than 120 years, the USGS has evolved from a small group of scientists who collected data and provided guidance on how to parcel, manage, and use the public lands of the West to an agency comprised of thousands of scientists who conduct research and assessment activities on complex scientific issues at scales ranging from the local to the global. The USGS will no doubt continue to evolve and adapt to meet changing national needs. In fact, the recent integration of the National Biological Service and parts of the U.S. Bureau of Mines into the USGS presents an ideal opportunity to examine the agency's vision, mission, role, and scientific opportunities as the organization begins the early years of the twenty-first century. The USGS recognized the need to adapt to changing demands when it asked the National Research Council (NRC) to undertake this study. The NRC formed a multidisciplinary committee of 16 experts to address issues related to the future roles, challenges, and opportunities of the agency.

A Review of the Proposed Revisions to the Federal Principles and Guidelines Water Resources Planning Document - National Research Council
Since it was issued in 1983, the federal document Economic and Environmental Principles and Guidelines for Water and Related Land Resources Implementation Studies (the P&G) has guided water resources project planning for four federal agencies. Since the early 1980s, however, there have been many changes in the national water resources planning landscape. In light of these developments, many groups – including committees of the National Research Council – have recommended that the P&G be reviewed and modernized. In 2007 the U.S. Congress directed the Secretary of the Army to revise the P&G. Congress also directed the Secretary to consult with other entities, including the National Academy of Sciences. The Council on Environmental Quality (CEQ) released its \

Disaster Risk Management in an Age of Climate Change: A Summary of the April 3, 2008 Workshop of the Disasters Roundtable - National Research Council (The National Academies Press, 2009)

Engineering and Environmental Challenges: Technical Symposium on Earth Systems Engineering - National Academy of Engineering (The National Academies Press, 2002)
Dealing with the challenges presented by climate change or rapid urban development require cooperation and expertise from engineering, social and natural sciences. Earth systems engineering is an emerging area of multidisclinary study that takes a holistic view of natural and human system interactions to better understand complex systems. It seeks to develop methods and tools that enable technically sound and ethically wise decisions. Engineering and Environmental Challenges presents the proceedings of a National Academy of Engineering public symposium on Earth systems engineering.

Reducing the Health Impacts of the Nitrogen Problem: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Nitrogen fertilizer is used extensively in the United States to maximize crop yields. As an essential nutrient to plant growth, nitrogen is a critical input to enhance agricultural productivity. However, excess nitrogen can leach into soil and water and contaminate drinking water sources with nitrate, a water-soluble chemical compound of nitrogen. Too much nitrate consumption can pose a health risk. Users of public drinking water supplies and private wells in areas surrounded by farmland are particularly vulnerable to exposure to nitrate in their drinking water. The workshop Reducing the Health Impacts of the Nitrogen Problem, held over five weekly virtual sessions from January 28 to February 25, 2021, provided a venue to discuss opportunities for reducing exposure to nitrate from agricultural sources in drinking water. More than 50 experts with backgrounds in agriculture, public health, economics, policy, engineering, water, social science, and other fields shared their perspectives through presentations and moderated discussions. This Proceedings of a Workshop-in Brief provides the rapporteurs' high-level summary of the topics and suggestions for potential actions to address challenges surrounding human exposure to nitrate from agricultural sources through drinking water, as discussed at the workshop itself.

Pathways to Urban Sustainability: Research and Development on Urban Systems: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
More than half of the world's people now live in cities. In the United States, the figure is 80 percent. It is worthwhile to consider how this trend of increased urbanization, if inevitable, could be made more sustainable. One fundamental shortcoming of urban research and programs is that they sometimes fail to recognize urban areas as systems. Current institutions and actors are not accustomed to exploring human-environment interactions, particularly at an urban-scale. The fact is that these issues involve complex interactions, many of which are not yet fully understood. Thus a key challenge for the 21st century is this: How can we develop sustainable urban systems that provide healthy, safe and affordable environments for the growing number of Americans living in cities and their surrounding metropolitan areas? To address this question, the National Research Council organized a workshop exploring the landscape of urban sustainability research programs in the United States. The workshop, summarized in this volume, was designed to allow participants to share information about the activities and planning efforts of federal agencies, along with related initiatives by universities, the private sector, nongovernmental groups, state and local agencies, and international organizations. Participants were encouraged to explore how urban sustainability can move beyond analyses devoted to single disciplines and sectors to systems-level thinking and effective interagency cooperation. To do this, participants examined areas of potential coordination among different R&D programs, with special consideration given to how the efforts of federal agencies can best complement and leverage the efforts of other key stakeholders. Pathways to Urban Sustainability offers a broad contextual summary of workshop presentations and discussions for distribution to federal agencies, regional organizations, academic institutions, think tanks and other groups engaged in urban research.

Groundwater Fluxes Across Interfaces - National Research Council (The National Academies Press, 2004)
Estimates of groundwater recharge and discharge rates are needed at many different scales for many different purposes. These include such tasks as evaluating landslide risks, managing groundwater resources, locating nuclear waste repositories, and estimating global budgets of water and greenhouse gasses. Groundwater Fluxes Across Interfaces focuses on scientific challenges in (1) the spatial and temporal variability of recharge and discharge, (2) how information at one scale can be used at another, and (3) the effects of groundwater on climate and vice versa.

Confronting the Nation's Water Problems: The Role of Research - National Research Council (The National Academies Press, 2004)
In order to confront the increasingly severe water problems faced by all parts of the country, the United States needs to make a new commitment to research on water resources. A new mechanism is needed to coordinate water research currently fragmented among nearly 20 federal agencies. Given the competition for water among farmers, communities, aquatic ecosystems and other users2014as well as emerging challenges such as climate change and the threat of waterborne diseases2014Confronting the Nation's Water Problems concludes that an additional 70 million in federal funding should go annually to water research. Funding should go specifically to the areas of water demand and use, water supply augmentation, and other institutional research topics. The book notes that overall federal funding for water research has been stagnant in real terms for the past 30 years and that the portion dedicated to research on water use and social science topics has declined considerably.

Land Use and Wildlife Resources (The National Academies Press, 1970)

River Science at the U.S. Geological Survey - National Research Council (The National Academies Press, 2007)

Science for Environmental Protection: The Road Ahead - National Research Council (The National Academies Press, 2012)
In anticipation of future environmental science and engineering challenges and technologic advances, EPA asked the National Research Council (NRC) to assess the overall capabilities of the agency to develop, obtain, and use the best available scientific and technologic information and tools to meet persistent, emerging, and future mission challenges and opportunities. Although the committee cannot predict with certainty what new environmental problems EPA will face in the next 10 years or more, it worked to identify some of the common drivers and common characteristics of problems that are likely to occur. Tensions inherent to the structure of EPA's work contribute to the current and persistent challenges faced by the agency, and meeting those challenges will require development of leading-edge scientific methods, tools, and technologies, and a more deliberate approach to systems thinking and interdisciplinary science. Science for Environmental Protection: The Road Ahead outlines a framework for building science for environmental protection in the 21st century and identified key areas where enhanced leadership and capacity can strengthen the agency's abilities to address current and emerging environmental challenges as well as take advantage of new tools and technologies to address them. The foundation of EPA science is strong, but the agency needs to continue to address numerous present and future challenges if it is to maintain its science leadership and meet its expanding mandates.

Review of the Desalination and Water Purification Technology Roadmap - National Research Council (The National Academies Press, 2004)
The Bureau of Reclamation and Sandia National Laboratories jointly developed the Roadmap to serve as a strategic research pathway for desalination and water purification technologies to meet future water needs. The book recommends that the Roadmap include a sharper focus on the research and technological advancements needed to reach the long-term objectives. The book also suggests that the environmental, economic, and social costs of energy required by increased dependence on desalination be examined. Strategies for implementing the Roadmap initiative are provided.

U.S. Army Corps of Engineers Water Resources Planning: A New Opportunity for Service - National Research Council (The National Academies Press, 2004)
From the Executive Summary: There are some concerns that the current Corps planning and construction budget has not kept pace with expanding national water management needs for flood hazard management, water transportation, and other purposes. At the same time, others question the wisdom of and budgetary prospects for the continuation of a traditional water project construction program. Debates about water use and funding priorities now extend to intense scrutiny of Corps of Engineers planning, investment, and project operations programs.

The Role of Science in Solving the Earth's Emerging Water Problems - National Academy of Sciences (The National Academies Press, 2005)
Earth is about 70% water, the human body is about 53% water, plants use water's unique properties to transport food, and aquatic organisms can survive during the winter due to water's thermal properties. However, as life continues to evolve on Earth, new problems with water emerge. The Sackler NAS Colloquium The Role of Science in Solving the Earth Emerging Water Problems provides a look into these problems ranging from water's agricultural use and importance in society to its scarcity and use in technology. (Sackler NAS Colloquium) The Role of Science in Solving the Earth Emerging Water Problems includes the colloquium, held October 8-14, 2004, program and abstracts of its presentations and posters. Also available in this book is the participant roster.

Responding to the Threat of Sea Level Rise: Proceedings of a Forum - National Academy of Engineering (The National Academies Press, 2017)
The future rate and extent of sea level rise are highly uncertain, and responses to higher water levels will need to reflect this uncertainty. Sea level rise was a major topic of the annual meeting of the National Academy of Engineering on October 9201310, 2016, and the second day featured a forum on adaptation to it. This summary of the forum, which also incorporates material from Robert J. Nicholls2019 plenary presentation, outlines a rich and challenging set of problems for engineers, scientists, and those who work with them.

Review of the WATERS Network Science Plan - National Research Council (The National Academies Press, 2010)
One of the most critical issues facing the United States today is the proper management of our water resources. Water availability and quality are changing due to increasing population, urbanization, and land use and climate change, and shortages in water supply have been increasing in frequency in many parts of the country. The National Science Foundation (NSF) has entertained the Water and Environmental Research Systems (WATERS) Network as one possible initiative whereby NSF could provide the advances in the basic science needed to respond effectively to the challenge of managing water resources. The WATERS Network, a joint initiative of the Engineering, the Geosciences, and the Social, Behavioral and Economic Sciences directorates at NSF, is envisioned as an integrated national network of observatories and experimental facilities supporting research, outreach, and education on large-scale, water-related environmental problems. The proposed observatories would provide researchers with access to linked sensing networks, data repositories, and computational tools connected through high-performance computing and telecommunications networks. This book, the final of a series about the WATERS project, provides a more detailed review of the Science Plan and provides advice on collaborating with other federal agencies.

Water Resources Planning for the Upper Mississippi River and Illinois Waterway - Transportation Research Board; National Research Council (The National Academies Press, 2005)
The U.S. Army Corps of Engineers recently completed its feasibility study for the Upper Mississippi River-Ilinois Waterway, which was one of the agency's longest and most complicated studies in its history. The first two reports from this WSTB committee reviewed analytical aspects of the Corps feasibility study. Water Resources Planning for the Upper Mississippi River and Illinois Waterway considers the broader issue of managing the multiple resources of the Upper Mississippi River and Illinois Waterway, especially with regard to several, recently-issued NRC reports on Corps of Engineers planning procedures. The report finds that a key issue regarding planning decisions on these river systems is the ambiguity related to several different pieces of legislation and acts that govern river management, and thus recommends that the administration and Congress clarify the federal intent for managing this river and waterway system. The report recommends an independent, retrospective reivew of the experience with a federal inter-agency Principals Group, which was convened to provide guidance to the Corps study. It is also recommended that the Corps strive to incorporate flexible, adaptive management principles through its entire water planning program, including operations of the lock and dam system.

Integrating Business Processes to Improve Travel Time Reliability - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2011)
TRB2019s second Strategic Highway Research Program (SHRP 2) Report: S2-L01-RR-1: Integrating Business Processes to Improve Travel Time Reliability addresses various ways that transportation agencies can reengineer their day-to-day business practices to help improve traffic operations, address nonrecurring traffic congestion, and improve the reliability of travel times delivered to roadway system users.The project that produced this report also produced SHRP 2 Report S2-L01-RR-2: Guide to Integrating Business Processes to Improve Travel Time Reliability.An e-book version of this report is available for purchase at Google, Amazon, and iTunes.

A Review of the Landscape Conservation Cooperatives - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The United States' tradition of conserving fish, wildlife, habitats, and cultural resources dates to the mid-19th century. States have long sought to manage fish and wildlife species within their borders, whereas many early federal conservation efforts focused on setting aside specific places as parks, sanctuaries, or reserves. With advances in landscape ecology over the past quarter-century, conservation planners, scientists, and practitioners began to stress the importance of conservation efforts at the scale of landscapes and seascapes. These larger areas were thought to harbor relatively large numbers of species that are likely to maintain population viability and sustain ecological processes and natural disturbance regimes - often considered critical factors in conserving biodiversity. By focusing conservation efforts at the level of whole ecosystems and landscape, practitioners can better attempt to conserve the vast majority of species in a particular ecosystem. Successfully addressing the large-scale, interlinked problems associated with landscape degradation will necessitate a planning process that bridges different scientific disciplines and across sectors, as well as an understanding of complexity, uncertainty, and the local context of conservation work. The landscape approach aims to develop shared conservation priorities across jurisdictions and across many resources to create a single, collaborative conservation effort that can meet stakeholder needs. Conservation of habitats, species, ecosystem services, and cultural resources in the face of multiple stressors requires governance structures that can bridge the geographic and jurisdictional boundaries of the complex socio-ecological systems in which landscape-level conservation occurs. The Landscape Conservation Cooperatives (LCC) Network was established to complement and add value to the many ongoing state, tribal, federal, and nongovernmental efforts to address the challenge of conserving species, habitats, ecosystem services, and cultural resources in the face of large-scale and long-term threats, including climate change. A Review of the Landscape Conservation Cooperatives evaluates the purpose, goals, and scientific merits of the LCC program within the context of similar programs, and whether the program has resulted in measurable improvements in the health of fish, wildlife, and their habitats.